Pengaruh Kehadiran dan Aktivitas Kelas Terhadap Perolehan Nilai Akhir Semester STIE Tri Dharma Nusantara - Andi Dorawati; Ronny Ahmad Asirie; Andi Abdul Razak Ishak (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2025)
The purpose of this study was to identify the influence of attendance and class activities on the final grades of students at STIE Tri Dharma Nusantara in Makassar. Sampling was conducted using the Slovin formula and simple random sampling method. The study used a one-way analysis model. This model is a development of multiple regression using the term endogenous variable (Y) with several exogenous variables (X). The results showed that attendance and class activities on the final grades of the semester had a significant influence, both partially at 0.700 or 70%, and simultaneously at 0.490 or 49% (on the R square or coefficient of determination) and a correlation of 0.411 or 41.1%, the effect is moderately positive.